Analisis Implementasi Pendidikan Karakter (PPK) melalui Program G7KAIH di Sekolah Dasar - Nurul Aini; Eddy Haryanto; Masbirorotni Masbirorotni (Varied Knowledge Journal, 2026)
This study analyzes the implementation of the Character Education Strengthening Policy (PPK) at SDN 131 Pematang Sulur, Jambi, focusing on the alignment between PPK as a normative framework and the Seven Habits of Highly Effective Indonesian Children (G7KAIH) as an operational strategy. A qualitative case study approach was employed, with data collected through semi structured interviews, non participatory observation, and document analysis. Data were analyzed interactively using triangulation to ensure validity. The findings indicate that PPK implementation occurs through four integrated approaches: classroom learning, school culture reinforcement, co curricular and extracurricular activities, and parental and community involvement. A systematic alignment between PPK and G7KAIH translates abstract values into concrete daily practices. Supporting factors include school leadership, teacher competence, positive school culture, and parental support, while inhibiting factors involve limited parental involvement, social and digital environmental influences, teachers’ conceptual understanding, and resource constraints. The impact of implementation varies across character dimensions, with stronger internalization observed for religiosity, nationalism, independence, and cooperation, while integrity remains relatively weak. Overall, PPK implementation is more effective in shaping habitual behavior than in developing moral reasoning, highlighting the importance of translating values into structured daily practices and ensuring strong synergy among school, family, and broader social contexts.